Self-control of ctudents in using the Internet - Putri, Yola Eka; Daharnis, Daharnis; Marjohan, Marjohan (Konselor, 2018)
This study sees a picture of student self-control in using the Internet. The research used is descriptive quantitative. The number of respondents in this study were 230 students. The instrument used was a questionnaire, the data were analyzed descriptively by determining the percentage of achievement using the average score percentage formula. The results of the study describe the overall control of BK UNP students in using the Internet in the high category. From the aspect of self-control it was found that: (1) cognitive control of students in using the internet was in the high category, (2) student behavior control in using the internet was in the moderate category, (3) control of student decisions in using the internet in the high.